ESTIMATION OF THE BEST LINEAR UNBISED PREDICTION (BLUP) OF KURDI RAMS FOR AVERAGE DAILY MILK YIELD DEPENDING ON THEIR PROGENY - & et al., Raoof (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at Erbil plain, Kurdistan region- Iraq during the period from July/2015 to June/2016. The study included 189 Kurdi ewes and 21 rams. The study aimed to estimate the Best Linear Unbiased Prediction (BLUP) values of sires for daily milk yield and to study the effect of the non-genetic factors (Age of dam, sex and type of birth, estrous sequences cycle and ewes weights at lambing) and to estimate the heritability and repeatability for average daily milk yield. The overall mean of daily milk production was 384.56g. The weight and age of dam showed a significant effect (p<0.05) on the daily milk yield. Ewes aged 5 years recorded a higher Milk yield (433.33gm) compared with ewes aged 2years (317.24gm). Heritability and repeatability estimates of daily milk yield were found to be 0.18 and 0.48 respectively. BLUP values for daily milk yield ranged between - 1.5265 and 1.9080. It could conclude from this study that most non- genetic factors has a significant impact on kurdi’s sheep performance and the expected genetic improvement based on the heritability estimate, since the repeatability of daily milk yield in this study is a high, the records of one lactation could be appropriate to estimate real acceptable productivity degree of accuracy, and can take a decision of culling among the animals without having to wait for the second season. Rams was evaluated genetically depending on the estimated values of the BLUP for the daily milk production, the presence of variation in genetic merit rams values means the possibility of exploiting the superior rams using artificial insemination to increase the rate of genetic improvement.